A Study of the Chinese Gender Gap in Financial Literacy - Alison Preston; Lili Qiu; Robert E. Wright (Institute of Labor Economics (IZA), 2022)
This paper uses data from the 2015 China Household Financial Survey to analyse the gender gap in financial literacy in China. The sample consists of 36,311 adult respondents. A variety of financial literacy measures are employed. We show that important predictors of financial literacy include age, education and geographic location and that there are strong cohort effects, with younger respondents significantly more financially literate than older respondents. Males, on average, are more financially literate than females. Blinder-Oaxaca decomposition analysis shows that the gender gap in financial literacy, in part, reflects gender differences in schooling that favours males. There are also large and significant urban-rural differences in financial literacy, with the gender gap markedly higher in rural areas. Overall the gender gap in financial literacy is largely unexplained by gender differences in characteristics. Indeed, were females in China to look like males in China (in terms of age and geographic location) the gender gap in financial literacy would be even wider. Policy responses are discussed in the paper.
Keywords: G53; I22; 330; financial literacy; decomposition; gender-gap; urban-rural gap; China